2012
DOI: 10.1177/0021955x12460043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two kinds of lignins, alkaline lignin and sodium lignosulfonate, on the foamability of thermoplastic zein-based bionanocomposites

Abstract: The aim of this study was to utilize zein, a protein from corn, to develop bioplastic formulations in combination with reactive additives based on ligninic compounds and to investigate the effects of these highly interactive additives on the foamability of zein. In particular, different amounts of alkaline lignin and sodium lignosulfonate were added to zein powder and poly(ethylene glycol) through melt mixing to achieve thermoplastic bio-polymers, which were subsequently foamed in a batch process, with a mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Two peaks at 2θ = 9.5 and 20° positions were related to two d -spacings around 4.6 Å ( d 0 ) and 8.96 Å ( d i ). Olivero et al 23 suggested that these two peaks are attributed to the average backbone distance within α-helix structure of the protein and d -spacing of α-interhelix packing, respectively, and they observed these two peaks in thermoplastic zein foam nanocomposite modified with 10 g/100 g AL and LSS. Compared with the control film, the lower intensity of modified films with lignin showed the hierarchical changes in SPI matrix due to the addition of lignin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two peaks at 2θ = 9.5 and 20° positions were related to two d -spacings around 4.6 Å ( d 0 ) and 8.96 Å ( d i ). Olivero et al 23 suggested that these two peaks are attributed to the average backbone distance within α-helix structure of the protein and d -spacing of α-interhelix packing, respectively, and they observed these two peaks in thermoplastic zein foam nanocomposite modified with 10 g/100 g AL and LSS. Compared with the control film, the lower intensity of modified films with lignin showed the hierarchical changes in SPI matrix due to the addition of lignin.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction may be attributed to the disruption of α-interhelix packing. 23 The XRD spectra were well-matched to the FTIR spectra, indicating that the addition of lignin interrupted the secondary structure of the protein matrix according to the reduced intensity. The consistency in the general pattern implies that there is a high compatibility between lignin and enzymatically modified SPI matrix.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This represents a challenge to combine them with anionic molecules, which in turn are the most abundant between functional materials (i.e. 110,111 It is generally obtained as a by-product in the paper industry through separation from cellulose fibers. 103,104 The LDH structure is similar to that of brucite mineral, a magnesium hydroxide easy to find in nature.…”
Section: Nano-fillersmentioning
confidence: 99%
“…Lignin is another bio-based filler and represents together with starch, cellulose and hemicellulose, the most abundant renewable material on the earth. 110,111 It is generally obtained as a by-product in the paper industry through separation from cellulose fibers. Its morphology depends on the kind of process used for delignification.…”
Section: Nano-fillersmentioning
confidence: 99%
“…Previously, we have introduced thermoplasticized zein by melt mixing, and probed the role of both the molecular architecture of the protein and the nature of plasticizers on the chemo‐physical properties and the ability to withstand extreme elongational deformation during film processing . More recently, zein‐based nanocomposites with lignin derivatives have been developed and the interactions among the protein, the plasticizers, and the lignin derivatives analyzed to explain the protein structural changes and conformational modifications brought about by the lignin derivatives . Such modifications resulted in the improvement of mechanical, water sorption, and flame‐retardant properties paving the way to further exploitation of the materials in the emerging field of the biodegradable electronics.…”
Section: Introductionmentioning
confidence: 99%